Relações filogenéticas do complexo de espécies "Cichlasoma" facetum com clados da tribo Heroini (Perciformes: Cichlidae) - Autran, Felipe Colbert Tavares (2001)
The phylogenetic relationships between the "Cichlasoma" facetum species complex and clades of the tribe Heroini, subfamily Cichlasomatinae, including taxa of Central and North America, are examined. The analysis is uniquely based on morpho-osteology of twenty-one species and includes five unpublished characters; the others are taken from KULLANDER 's phylogenetic study (1998) and previous studies, in a total of twenty-nine characters in seventeen terminal taxa. From the five equally most parsimonius cladograms (length 84; consistency index 51; retention index 59 and rescaled consistency index 30), one obtains the tree of strict consensus with the following topology: (((Mesonauta + Pterophyllum) (Heros (Symphysodon + Uaru))) (("Cichlasoma" meeki + "C." nigrofasciatum) (("C." facetum species complex) (Hypselecara (("C." atromaculatum, "C." citrinellus) ("C." octofasciatum (Caquetaia + Petenia))))))). The monophyly of the tribe Heroini as proposed by KULLANDER (op. cit.) is corroborated by the apomorphic states of the characters related to the anal fin. The monophyly of the "C." facetum species complex is supported by two unpublished apomorphic conditions. The present phylogenetic hypothesis differs from the most recent one, proposed by KULLANDER (op. cit.) for the neotropical cichlids through nevralgic, miologic and osteologic studies.